The Automotive Industry in Mexico and China: Complementary opportunities - Gachúz, Juan Carlos; Montes, María Paula (Latin American Journal of Trade Policy, 2020)
China has become the mayor producer of vehicles worldwide and the main companies in the country began to expand globally. The presence of Chinese companies in the automotive industry in Mexico represents an opportunity for complementarity, expansion and development of the sector for both countries. The arrival of Chinese companies BAIC and JAC to Mexico has positively impacted the sector in terms of investment, employment and infrastructure. China’s foreign direct investment in the Mexican automotive industry increases the production capacity of the sector in Mexico and represents a medium-term opportunity to increase exports in the sector.